PEMBANGUNAN TAMAN BACAAN RAKYAT BANJAR WIJAYA - Widodo Kushartomo; Christopher Kevin Sidharta; Charles Brianjaya; Prem Singh (PROSIDING SERINA, 2021)
Civil Engineering Undergraduate Study Program and  Tarumanagara University Research and Community Service Institute in collaboration with residents of RW 07 Banjar Wijaya, Cipete sub-distric, Tangerang City, presented a library building, hereinafter referred to as Banjar Wijaya People's Reading Park. The reading park is a place that is needed by the community around the location as a place to get information, knowledge and a place for refreshing. The Covid-19 pandemic has limited the activities of the community in carrying out activities, including school children. Children who are still sitting in the education bench in RW 07 Banjar Wijaya, Cipete Village, Tangerang City, experience bore and difficulty in completing school assignments. Lack of information and guidance and boredom due to restrictions make children play more gadgets and don't care about lessons or school assignments. Children tend to be more disappointed when reminded not to play with gadgets and have to complete schoolwork. The People's reading park was presented in the community of RW 07 Banjar Wijaya to help overcome the complaints of parents who have school-age children. The existence of the Banjar Wijaya Reading Park is very helpful for children in completing assignments from school, increasing knowledge and a place to socialize. The presence of the reading park is used as a place for playing and entertainment for children to get to know more about the diversity of the culture, folklore and so on through the books provided, both physically and digitally.